Studying the state of readiness of institutions and units of medical supply of the armed forces of Ukraine for the implementation of logistics information system - M. V. Bilous; O. A. Ryzhov; O. P. Shmatenko (The State Expert Center of the Ministry of Health of Ukraine, 2020)
The problem of implementing an information system to implement effective logistic management of streaming processes in the medical service of the Armed Forces of Ukraine and gaining functional compatibility with the medical services of the Armed Forces of the NATO member countries is relevant and requires detailed study. The aim of the work is study of the state of readiness of institutions and units of medical supply of the Armed Forces of Ukraine for the implementation of the logistics information system by expert survey. The analysis of domestic and foreign scientific literature, the current regulatory framework of Ukraine, the results of the expert survey was conducted to achieve the aim of the study. During the research, methods of information retrieval, systematization, content analysis, expert survey, comparison, generalization, mathematical-statistical and graphical modeling were used. The article analyzes the results of an expert survey on certain aspects of the practical implementation of information logistics in managing the medical supply of the Armed Forces of Ukraine. The experts were medical servicemen and employees of the Armed Forces of Ukraine, who are involved in the medical supply system of the troops. The analysis showed that currently the documents of the movement and accounting of medical supplies in institutions and units of medical supply of the Armed Forces of Ukraine is carried out both in paper and electronic format. Experts noted that for certain forms there is a duplication of documents, so the extra time is used. At those workplaces where paper work takes place (45%), there are no computers at all. Computers located at expert workplaces are connected to local networks or have Internet access only in 48% of respondents. It is established that in the functioning of institutions and units of the medical supply of the Armed Forces of Ukraine there is not automatic identification technology - RFID. It was found that 79% of respondents lack professional automated control systems (ACS). Some institutions and units of the medical supply of the Armed Forces of Ukraine have an automatic control system «Dnipro». However, it is emphasized that computers and ACS are unstable. An analysis of the results of the expert survey made it possible to determine that the primary task in the context of introducing the logistics information system is to provide modern computer equipment for the institutions and units of the medical supply of the Armed Forces of Ukraine. At the same time, there is a need to increase the level of skills in working with computer equipment of the personnel of the medical supply system of the Armed Forces of Ukraine, who are involved in using computer technologies. The need for the development of modern decision support software for managing streaming processes in the medical supply system of the Armed Forces of Ukraine is established. As well as the introduction of a program for the automatic accounting of medical supplies, which will be synchronized with the Medical Forces Command, institutions and medical supply units of the Armed Forces of Ukraine. At the same time, the specified software should have a single interface with the Armed Forces of NATO member states.